Teacher Challenges in Implementing Deep Learning in Elementary Mathematics - Nurcahyono, Novi Andri; Sagita, Sylva; Syam, Aldo Redho; Ariyatun, Ariyatun (Proceedings of Forum for University Scholars in Interdisciplinary Opportunities and Networking, 2025)
The deep learning approach is a learning strategy that emphasizes conceptual understanding, critical thinking, and problem-solving skills. In the context of elementary school mathematics learning, this approach is increasingly important to equip students with meaningful and applicable mathematical competencies in real life situations. However, the implementation of deep learning in mathematics instruction still faces various challenges. This article aims to identify and analyze the barriers to applying the deep learning approach in elementary school mathematics learning. The review was conducted through a literature study of journal articles obtained from Google Scholar. From the initial search results, 12 journal articles were identified that met the inclusion criteria and were suitable for analysis. The findings indicate several obstacles, including limited instructional time that does not support exploratory learning processes, insufficient interactive facilities and media, and teachers’ limited understanding of the essence of deep learning. In addition, a curriculum that remains oriented toward procedural memorization and a conservative school culture reinforce resistance to innovative approaches. Students’ unpreparedness in dealing with exploratory methods also emerges as a significant challenge. The implications of these findings highlight that implementing deep learning in elementary mathematics requires systemic reforms, including continuous teacher training, strengthened learning infrastructure, and consistent policy support. Consequently, mathematics learning should not only focus on mastering formulas but also foster reflective thinking and contextual problem-solving skills relevant to everyday life.